2015
DOI: 10.4236/ijcm.2015.610103
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cytokine Profiles of Chronic Fatigue Syndrome/Myalgic Encephalomyelitis and Multiple Sclerosis Patients

Abstract: Background: Chronic Fatigue Syndrome, also known as Myalgic Encephalomyelitis (CFS/ME), is a debilitating condition that presents with a range of symptoms, including fatigue, cognitive dysfunction, muscular and joint pain, and may be immune-mediated. In particular, patients exhibit abnormal cytokine expression. Similarly, in Multiple Sclerosis (MS), patients display neuroimmunological symptoms, and abnormal cytokine expression, with some overlap in symptomology with CFS/ME. The purpose of this study was to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
2
5
0
Order By: Relevance
“…Our finding, especially in light of the extremely low effect size, fits with the more recent view by the Institute of Medicine of the National Academies (2015) that in and of itself CFS is best not viewed as a somatized manifestation of a mental health condition (see also review by Underhill, 2015). The shift to a greater conviction in the organic basis of CFS has been influenced not only by the controversy engendered by the PACE study but also by advancements in research confirming hypotheses regarding the role of immune system dysfunction among individuals with CFS (e.g., Hardcastle et al, 2015;Hornig et al, 2015;Wong et. al, 2015).…”
Section: Failure To Support Hypothesis Of Greater Imh Prevalence Insupporting
confidence: 85%
See 1 more Smart Citation
“…Our finding, especially in light of the extremely low effect size, fits with the more recent view by the Institute of Medicine of the National Academies (2015) that in and of itself CFS is best not viewed as a somatized manifestation of a mental health condition (see also review by Underhill, 2015). The shift to a greater conviction in the organic basis of CFS has been influenced not only by the controversy engendered by the PACE study but also by advancements in research confirming hypotheses regarding the role of immune system dysfunction among individuals with CFS (e.g., Hardcastle et al, 2015;Hornig et al, 2015;Wong et. al, 2015).…”
Section: Failure To Support Hypothesis Of Greater Imh Prevalence Insupporting
confidence: 85%
“…The shift to a greater conviction in the organic basis of CFS has been influenced not only by the controversy engendered by the PACE study but also by advancements in research confirming hypotheses regarding the role of immune system dysfunction among individuals with CFS (e.g., Hardcastle et al, ; Hornig et al, ; Wong et. al, ). Even psychoanalytic clinicians have begun to recognize the importance of not attributing psychological/emotional etiology to CFS symptoms, lest patients experience their suffering to be invalidated, misunderstood, and stigmatized (Gurwitt, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the measurement of the plasmatic concentrations of proinflammatory cytokines showed a significantly higher level of IFN-γ in MS patients compared to healthy individuals. This was expected, since IFN-γ is a proinflammatory cytokine whose role in the pathophysiology of MS has been demonstrated [9]. Furthermore, we found significantly lower amounts of IFN-γ in patients treated with GA compared with patients treated with IFN-β.…”
Section: Discussionsupporting
confidence: 73%
“…The participation of proinflammatory cytokines, such as IL-4, IL-6, IL-23, IL-27, IL-17, and IFN-γ, in the progression of the disease has also been reported. Plasmatic IFN-γ levels have been reported to increase in MS patients [9], associated with periods of relapse and a worsening of disease symptoms [10], as well as with fatigue and depression [11]. MS is assumed to be a T-helper 1 (Th1)/Th17-mediated autoimmune disease [12].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated level of this cytokine was interpreted as a dysfunction of NK cells activity and imbalance of Th1/Th2 ratio. Accordingly, this cytokine might be considered as one of the markers for MS pathogenesis (Wong et al, 2015). The investigated IL-12 was also evaluated in terms of EDSS, and the results suggested that serum level of this cytokine might not be influenced by EDSS.…”
Section: Statistical Analysis:-mentioning
confidence: 99%